Electrophoretic patterns of sarcoplasmic proteins in carangid fishes - Verghese, Bindu; Jayasankar, P (Indian Journal of Fisheries, 2011)
The present paper reports muscle myogen patterns of four species of carangids,viz. Decapterus russelli, D. macrosoma, Selar crumenophthalmus and Megalaspiscordyla using horizontal slab polyacrylamide gel electrophoresis. The number ofprotein fractions (presumptive loci) in the muscle of D. russelli, D. macrosoma,S. crumenophthalmus and M. cordyla were found to be 9, 7, 6 and 5, respectively.The Rf value ranged from 21 to 84 in S. crumenophthalmus, 2 to 72 in M. cordyla,15 to 89 in D. macrosoma and 18 to 96 in D. russelli. The difference in numberof fractions, their mobility pattern and staining indicated species-specificity. Withthe limited number of samples used in our study, there has been an indicationof intraspecific polymorphism among three species of carangids, being 3.5% in D.russelli, 13.5% in D. macrosoma and 6.6% in S. crumenophthalmus. M. cordylashowed no intraspecific polymorphism. The study reveals that protein fractionsin carangids can be used as species-specific markers, which could be helpful inresolving disputes in the event of any taxonomic ambiguity